Pengaruh Sikap Generasi Milenial dan Generasi Z terhadap Kecenderungan untuk Terus Menggunakan Teknologi Kecerdasan Buatan - Khemiko Khemiko; Yoke Pribadi Kornarius; Angela Caroline; Triningtyas Elisabeth Putri Gusti; Agus Gunawan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study aims to investigate the influence of millennials' and generation Z's attitudes on their intention to continue using artificial intelligence (AI) technology. Data was collected through a questionnaire distributed online to individuals working in various fields of work that use AI in their activities. A total of 140 questionnaires were returned, exceeding the minimum sample size requested. Data processing involved validity and reliability tests, classical assumption tests, and regression tests. The results showed that millennials tend to have a skeptical attitude towards AI capabilities, while generation Z is more open to the use of AI in various aspects of life. Regression analysis showed that a positive attitude towards AI significantly influences the intention to continue using the technology. The study also revealed that human happiness is more related to human aspects than the use of AI technology. As such, the findings provide valuable insights into the complexity of human interactions with AI and the implications for future technology adoption.